System analysis based on the lysosome-related genes identifies HPS4 as a novel therapy target for liver hepatocellular carcinoma - He, Ke‐Jie; Nie, Zhiqiang (Frontiers in Oncology, 2023)
Abstract Background Liver cancer is a leading cause of cancer-related deaths worldwide. Lysosomal dysfunction is implicated in cancer progression, however prognostic prediction models based on lysosome-related genes (LRGs) are lacking in liver cancer. This study aimed to establish an LRG-based model to improve prognosis prediction and explore potential therapeutic targets in liver cancer. Methods Expression profiles of 61 LRGs were analyzed in The Cancer Genome Atlas liver cancer cohorts. Fourteen LRGs were identified and their association with clinical outcomes was evaluated. Unsupervised clustering, cox regression, and functional assays were performed. Results Patients were classified into high-risk and low-risk subgroups based on 14 LRGs. The high-risk group had significantly worse overall survival. Aberrant immune infiltration and checkpoint expression were observed in the high-risk group. Furthermore, HPS4 was identified as an independent prognostic indicator. Knockdown of HPS4 suppressed liver cancer cell proliferation and induced apoptosis. Conclusions This study developed an LRG-based prognostic model to improve risk stratification in liver cancer. The potential value of HPS4 as a therapeutic target and biomarker was demonstrated. Regulation of HPS4 may offer novel strategies for precision treatment in liver cancer patients.